IMPLEMENTASI MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN MENGGUNAKAN MEDIA FLASHCARD PADA PENDIDIKAN AGAMA ISLAM DI SMP YAPENAS GEMPOL PASURUAN - Sintia Nor Alfiatul Qomaria; Saifulah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the implementation of the Snowball Throwing learning model using flashcard media to improve students’ understanding of Islamic Religious Education in Grades VII and VIII at SMP Yapenas Gempol. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation, involving Islamic Religious Education teachers and students as subjects. The findings indicate that the learning model was implemented through structured stages of planning, implementation, and evaluation, with flashcards serving as a tool to present questions and reinforce students’ comprehension. The learning process was active, participatory, and enjoyable, making it easier for students to understand the material, boosting their confidence in answering questions, and improving their academic performance as seen in both classroom assessments and daily tests. Therefore, the implementation of the Snowball Throwing model supported by flashcards has proven effective in enhancing students’ understanding of Islamic Religious Education.